The Information Sources Preferences Towards Preparation for The Olympiad of National Science among High School Students in The City of Surabaya - Husnaeni Rohmawati (Universitas Airlangga, 2022)
The preference of information sources in preparation for the National Science Olympiad among high school students in the city of Surabaya, has the aim of explaining and knowing how the preferences or selection of information sources among high school students are to prepare themselves to confront OSN. The number of sources of information widespread among high school students will lead to a choice of information sources that can later be used as references by students to meet academic needs and for the needs of the National Science Olympiad (OSN). The ability of students to access and obtain information sources effectively can be a provision that must be mastered by students in selecting information sources. That way, students will get sources of information according to their needs in preparing for OSN. This research uses descriptive quantitative research methods and purposive sampling. The data collection method was taken from questionnaires and secondary data. This study analyzes the selection of printed and non-printed sources of information and the factors behind respondents choosing information sources. The results obtained from this research are that students tend to have multiple preferences, it can be proven by as many as 49% of respondents choosing to use both sources of information (printed and non-printed), this shows different results from previous research and uses as the theory of this research proposed by Jhon Steppen B. Arenas, et al. .al. (2018) The factors behind the choice of information sources available by students are due to the availability of collections in locations where students make choices, and also the convenience provided when selecting information sources, both printed and non-printed sources of information to prepare for the National Science Olympiad ( OSN). The selection of information sources is also inseparable from the important role of the library, as a location to find sources of information that can support OSN preparation.